2022
DOI: 10.4254/wjh.v14.i7.1291
|View full text |Cite
|
Sign up to set email alerts
|

Hepatogenous diabetes: Knowledge, evidence, and skepticism

Abstract: The diabetogenic potential of liver cirrhosis (LC) has been known for a long time, and the name "hepatogenous diabetes" (HD) was coined in 1906 to define the condition. Diabetes mellitus (DM) that develops as a consequence of LC is referred to as HD. In patients with LC, the prevalence rates of HD have been reported to vary from 21% to 57%. The pathophysiological basis of HD seems to involve insulin resistance (IR) and pancreatic β-cell dysfunction. The neurohormonal changes, endotoxemia, and chronic inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 135 publications
0
11
0
Order By: Relevance
“…Increased IR have been observed in both patients with liver cirrhosis and sepsis. In patients with liver cirrhosis, the pathophysiological mechanisms of IR remain partly understood, hyperinsulinemia resulted from decreased hepatic extraction and portosystemic shunting of insulin have been associated with high IR (2). In patients with sepsis, increased cytokines, cortisol, growth hormone, and catecholamine levels likely have a role in the development of IR (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased IR have been observed in both patients with liver cirrhosis and sepsis. In patients with liver cirrhosis, the pathophysiological mechanisms of IR remain partly understood, hyperinsulinemia resulted from decreased hepatic extraction and portosystemic shunting of insulin have been associated with high IR (2). In patients with sepsis, increased cytokines, cortisol, growth hormone, and catecholamine levels likely have a role in the development of IR (24).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we have also found that diabetes was associated with poor short-term prognosis in patients with acute-on-chronic liver failure (ACLF)(6). It has been suggested that liver dysfunction had "toxic effect" on pancreatic β-cell and diabetes resulted from impaired pancreatic β-cell function and increased insulin resistance (IR) in patients with liver cirrhosis (2,7), however, the evidences to support this hypothesis are still scare. Hyperglycemia has also been found in patients with acute hepatitis, acute liver failure and sepsis(8-10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver cirrhosis and T2DM are common chronic diseases that are interrelated. The development of liver cirrhosis causes dysfunction in the receptors of the liver and pancreas, which leads to decreased insulin binding, resulting in insulin resistance and therefore the development of T2DM [7]. Cytokines may act as an important factor affecting the co-occurrence of the two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Intestinal dysbiosis, hyperammonemia, sarcopenia, and other factors may also contribute to the pathogenesis of HD. [11]…”
Section: Introductionmentioning
confidence: 99%